A Confinement‐Driven Nucleation Mechanism of Metal Oxide Nanoparticles Obtained via Thermal Decomposition in Organic Media. Issue 20 (15th April 2022) - Cotin, Geoffrey; Heinrich, Benoît; Perton, Francis; Kiefer, Céline; Francius, Gregory; Mertz, Damien; Freis, Barbara; Pichon, Benoit; Strub, Jean‐Marc; Cianférani, Sarah; Ortiz Peña, Nathalie; Ihiawakrim, Dris; et al.
Abstract: Thermal decomposition is a very efficient synthesis strategy to obtain nanosized metal oxides with controlled structures and properties. For the iron oxide nanoparticle synthesis, it allows an easy tuning of the nanoparticle's size, shape, and composition, which is often explained by the LaMer theory involving a clear separation between nucleation and growth steps. Here, the events before the nucleation of iron oxide nanocrystals are investigated by combining different complementary in situ characterization techniques. These characterizations are carried out not only on powdered iron stearate precursors but also on a preheated liquid reaction mixture. They reveal a new nucleation mechanism for the thermal decomposition method: instead of a homogeneous nucleation, the nucleation occurs within vesicle‐like‐nanoreactors confining the reactants. The different steps are: 1) the melting and coalescence of iron stearate particles, leading to "droplet‐shaped nanostructures" acting as nanoreactors; 2) the formation of a hitherto unobserved iron stearate crystalline phase within the nucleation temperature range, simultaneously with stearate chains loss and Fe(III) to Fe(II) reduction; 3) the formation of iron oxide nuclei inside the nanoreactors, which are then ejected from them. This mechanism paves the way toward a better mastering of the metal oxide nanoparticles synthesis and the control of their properties. Abstract : A nucleation mechanism of iron oxide nanoparticles synthesized by a thermal decomposition method is presented: instead of a homogeneous nucleation within the solvent, the nucleation occurs within vesicle‐like‐nanoreactors. The different steps are: 1) melting and coalescence of iron stearate particles into droplet‐shaped nanoreactors; 2) formation of a hitherto unobserved iron stearate crystalline phase; 3) formation of iron oxide nuclei inside the nanoreactors.